NUTRITIONAL STRATEGIES FOR ENHANCING SKIN MICROBIOME HEALTH: A REVIEW OF DIET AND DERMATOLOGICAL OUTCOMES (The Research of Medical Science Review, 2025)
This narrative review highlights recent research on the impact of dietary practices on skin microbiomes and their associated dermatological effects. The skin microbiome, composed of various bacteria, fungi, and viruses, plays a crucial role in immune regulation and maintaining barrier function. Dysbiosis in this ecosystem has been linked to conditions such as psoriasis, atopic dermatitis, acne, and premature aging. We carried out comprehensive search on Google Scholar, PubMed, and ScienceDirect for open-access review papers published between 2015 and 2024. Our study centered on the relationships among probiotics, prebiotics, certain micronutrients and their impact on skin health. A total of ten articles that fulfilled the inclusion criteria were examined thematically. Research indicates that the intake of probiotics and prebiotics from fibre- rich foods, as well as products like kefir, kimchi, and yogurt, can enhance skin hydration and barrier integrity, and reduce systemic inflammation. Essential micronutrients operate through various mechanisms: zinc is involved in anti-inflammatory processes and promotes epithelial repair, while copper and selenium support antioxidant defences and tissue remodeling; Vitamin D plays a role in enhancing innate immunity; vitamins C and E serve as antioxidants, promoting collagen synthesis and decreasing UV damage; additionally, vitamin A and its derivatives control the differentiation of keratinocytes and lessen acne lesions. Dietary approaches like the Mediterranean diet and those based on plants, rich in polyphenols, unsaturated fats, and fibers, are linked to improved microbial health. Diverse diets are linked to milder skin conditions, while Western diets high in refined sugars and fats worsen inflammation and imbalances in gut bacteria. These findings highlight the importance of personalized dietary approaches and indicate the need for further clinical research to clarify causation and establish dosage recommendations, reinforcing the role of nutrition as a non-pharmacological method to enhance skin microbiota health.